Evaluative language in sports : crowds, coaches, and commentators - Walsh, John (Linguist); Caldwell, David (Linguist); Jureidini, Jon (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"Walsh, Caldwell and Jureidini offer an expansive linguistic perspective on the evaluative language prevalent in the world of professional sports. This book presents a close linguistic analysis of evaluative language in sport. Drawing on appraisal theory and data from three distinct sporting contexts - songs and chants in football stadiums, television commentary, and coach discourse - it examines the critical role played by affectual, judgemental and appreciative language. In the spirit of sociolinguistics, this book also considers the history and culture of the respective sporting contexts. Connections are made between the evaluative language expressed by supporters, commentators and coaches and the invocation of power and solidarity. Evaluative Language in Sports gives insight into some of the key language practices that contribute to professional sports culture: a communal and combative world of winners and losers, 'us and 'them'. An innovative and valuable book that will appeal to students, researchers and sports enthusiasts interested in sports communication and language, sociolinguistics and media studies"--
Sports discourse -- Singing and chanting -- Television commentary -- Coaching -- Exploring attitude in sport.
Keywords: English language -- Discourse analysis; English language -- Social aspects; Sports -- Language; Sports -- Terminology; Communication in sports; Evaluation (Linguistics); Appraisal (Linguistics); LANGUAGE ARTS & DISCIPLINES / Communication; LANGUAGE ARTS & DISCIPLINES / Linguistics; LANGUAGE ARTS & DISCIPLINES / General